Factors influencing postdatism and fetomaternal outcomes in postdated pregnancies: a prospective study on spontaneous and induced labor - Phogat, Akshita; Agarwal, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This study aimed to identify factors contributing to postdates and evaluate fetomaternal outcomes in postdated pregnancies undergoing spontaneous and induced labor. Methods: This prospective study at Kasturba Hospital, Delhi (January-December 2023), involved 158 pregnant women beyond 40 weeks, divided into induction of labor (IOL) and spontaneous labor (SPOL) groups. Inclusion criteria included pregnancies beyond 40 weeks, confirmed gestational age, singleton cephalic presentation, and no complications. Maternal factors such as parity, demographics, BMI, and outcomes like mode of delivery, labor duration, and complications were recorded. Fetal outcomes, including APGAR scores and NICU admissions, were also analysed. Results: Most participants were under 24 years old, with a mean BMI of 23.51±2.90 kg/m². Primigravida women made up 58.86% of the study population. Cesarean rates were higher in the IOL group (62.02%) than in the SPOL group (21.5%), with more postpartum hemorrhage in the IOL group (18.98% versus 3.79%). Fetal outcomes showed no significant differences, though meconium-stained amniotic fluid and NICU admissions were higher in the IOL group. Conclusions: Primiparity, obesity, and a history of postdatism are significant factors associated with postdated pregnancies. While induction of labor is linked to higher cesarean rates and increased postpartum haemorrhage, fetal outcomes are similar to those in spontaneous labor. Individualized management and accurate gestational age estimation are essential. Further research is needed to optimize outcomes for postdated pregnancies.